From Web to Web 2.0 and e-Learning 2.0 - Coutinho, Clara Pereira (2009)
In this chapter the authors analyze issues and ideas regarding the next generation of e-Learning, which is already known as e-Learning 2.0 or social e-Learning. They will look at the new learning tools that have emerged from the evolution of the Web, to the Web 2.0 paradigm, discussing their potential for supporting modern and independent lifelong learners. Even more important, the authors will justify the modeling of a new concept for the future of teaching and learning in the knowledge-based society in which we live. The conclusion will present a scenario for the evolution of the Web, the Semantic Web or 3.0 generation Web, which is emerging as a higher environment that will advance the design and development of e-Learning systems in promising new directions: machine-understandable educational material will be the basis for machines that automatically use and interpret information for the benefit of authors and educators, making e-Learning platforms more adaptable and responsive to each individual learner.